Tinjauan Yuridis Terhadap Visum Et Repertum Dalam Pembuktian Tindak Pidana Penganiayaan: (Studi Kasus Putusan Nomor: 221/Pid.B/2022/PN.Mtr.) - Dhammananda; Sari Lukman, Dwi Ratna Kamala; Ernita Ratnadewi, Ni Nyoman (Metta : Jurnal Ilmu Multidisiplin, 2023)
This research was carried out with the aim of knowing and analyzing the legal force of Visum et Repertum and analyzing how the basic considerations of judges in deciding criminal cases of persecution in decision number: 221/Pid.B/2022/PN.Mtr. This is because in this decision the defendant was sentenced to imprisonment for 7 (seven) months reduced while the defendant was in detention to 5 (five) months and 10 (ten) days. According to the authors, the sentence was light enough considering that the victim did not only suffer immaterial losses in the form of pain due to the abuse but also suffered material losses which caused the victim to be unable to move for 1 (one) month and unable to carry out her job as a go-kart driver. The method used is a normative research method with legal material collection techniques through literature studies and documentation studies. Furthermore, using descriptive analysis by describing, analyzing, concluding and reporting the research results obtained. The theory used is the theory of evidence and relative theory. The results of the study show that Visum et Repertum has the same legal force as other evidence, but in making a decision the element of the Judge's belief is the most decisive thing about the guilt or innocence of the defendant with at least 2 (two) pieces of evidence as the basis for the Judge's consideration. Judge's consideration in decision Number: 221/Pid.B/2022/PN.Mtr. based on witness testimony, expert testimony, and documentary evidence in the form of the results of the Visum et Repertum examination stating that the victim was truly injured. The basis for the Visum et Repertum is Visum et Repertum Number: VER: Sket/Ver/324/XII/2021/Rumkit signed by the examining doctor, dr. Dyah Mayang Ramadhani.